Content Analysis of Travelogues from the Qajar Era - Manochehr Akbari; Saeed Alaei (Matn/Pizhūhī-i Adabī, 2024)
Travelogues are valuable artifacts that provide firsthand accounts of historical, social, cultural, religious, and literary events. They offer a comprehensive perspective for examination from multiple angles. In ancient Persian literature, travel writing has a rich historical tradition. Approximately a millennium has elapsed since the composition of Nasser Khosrow's travelogue. Subsequently, several travelogues have been authored, serving as compelling evidence of the authors' meticulousness and the audience's profound fascination with this genre of literature. During the Qajar dynasty, travelogue writing played a significant role. Travelogue writing has never been as popular as it is in today's age. Each author in these travelogues examined travel concerns and events from a distinct perspective, focusing on particular aspects. During the Qajar era, the proliferation of this genre of literature led several intellectuals to use travelogues as a means of disseminating information and documenting historical occurrences. The present research has focused on extracting and analyzing prevalent topics and themes in travelogues from this era. To achieve this, we have carefully chosen a selection of significant and comprehensive travelogues from this time period. After a thorough examination of their content, we identified the shared characteristics and themes present in these travelogues. Surveys indicate that these subjects are prevalent in the majority of trip narratives: 1. Worship and adoration of God 2. Explanation 3. Evaluation 4. Inconsistency 5. Providing insufficient information 6. Describing the present circumstances and articulating spiritual states 7. Remorse for one's native land.1. IntroductionA travelogue is a form of written account where the author provides a detailed description of their observations regarding the state of the cities or territories they have visited. These sightings and hearings encompass a variety of factors, including geographical location, weather conditions, population demographics, spoken language, religious beliefs, national and religious customs, esteemed elders, and renowned personalities. Furthermore, the author delineates the cities, structures, thoroughfares, marvels, and other elements, furnishing the readers with pertinent details.Within ancient Persian literature, travel writing has a rich historical tradition. Approximately a millennium has elapsed since the composition of Nasser Khosrow's travelogue. Since then, authors have penned several travelogues, demonstrating their meticulousness and the audience's profound fascination with this literary form.An examination of the historical origins of travelogues in Iran reveals their ancient nature in comparison to other forms of literature. To document the history of travelogue writing and the origins of tourism in ancient Iran, it is necessary to delve into the pre-settlement era of Iranians. Historical evidence indicates that there was a longstanding exchange between tribes on this plateau prior to the establishment of Iranian settlements. Following the Mongol invasion, traditional travel writing experienced a decline. However, with the restoration of Iran's governmental unity during the Safavid era, European visitors produced a multitude of travelogues documenting their journeys to Iran.Travelogue writing gained prominence during the Qajar era. This was primarily due to the political ties with Europe and the prevailing political, social, and economic circumstances that compelled people to leave their homeland. In response to these conditions, the written format of travelogues became widespread.This research aims to analyze and investigate the travelogues of this era from multiple perspectives, including literary, sociological, and historical. However, the primary objective, as perceived by the author, is to examine the content and identify recurring themes in these travelogues.2. Literature ReviewThe study of travelogues has been the subject of numerous publications, including books, articles, and research papers. A few examples are included below:Fouad Farooqi's book "Survey in Travelogues" (1361) is an exceptionally detailed work on travelogues.In his work "Travellers of History: A Review of the History of Travel and Tourism in Iran," Masoud Nourbakhsh thoroughly examines the history of travel and travel literature."From biography writing to narrative writing (2015)" by Qudsieh Rizvanian is a notable contribution to the subject of travel literature. In this book, the author provides comprehensive definitions of travel, travel writing, travel literature, and many genres of travel."Gholamhossein Yousefi's book "Deidari ba Ahl al-Qalam" (1367) includes an item named "Siri Dar Afaq" that delves into the genre of travelogue and travelogue writing.In his 2003 work "Haj Sayah's Travelogue," Mansour Tharwat analyzes the traveler's account in terms of its reporting methodology, significant aspects, unique observations, and literary style.3. MethodologyThis study uses content analysis to investigate writings from the Qajar period, utilizing available materials in libraries. The research focuses on analyzing a significant number of travelogues from this era, paying particular attention to identifying similar content traits.4. ConclusionAfter analyzing the travelogues from the Qajar era, it becomes apparent that the majority of these travelogues share common themes. These themes include description, criticism, contradictions, providing partial information, conveying personal situations, and expressing loss for one's nation.The authors of these travelogues meticulously documented the daily occurrences and provided concise depictions of every individual, location, mode of transportation, city, and residence they encountered.Tourists predominantly discussed the positive aspects of Westerners' lifestyles and openly expressed their love for these phenomena, while unfavorable and critical depictions were also present in these travelogues.The perception and reputation of these trip writers from the Western region were not entirely consistent, and they exhibited varied responses in this matter. The fluctuations in circumstances have been influenced by things such as employment, education, and the desire to explore new places.The advancements made by the Westerners greatly affected the trip writers and captured their attention.Travel writers have often expressed a strong desire for the lifestyle and opportunities available in the West while also feeling sorry for the state of their own hometown. Travel writers who transitioned from an underdeveloped nation to an emerging nation were unable to conceal their astonishment and reverence for the remarkable occurrences and industries they encountered in the Western world.